On deviations and defects of meromorphic functions of finite lower order - Marchenko, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain estimates for the sum of deviations and sum of defects to power 1/2 in terms of the Valiron defect of the derivative at zero. In particular, the Fuchs hypothesis (1958) is verified.